PHT making horticultural growers self-reliant - Krishna Rao, KP Gopala (Indian Horticulture, 2019)
The Post-Harvest Technology (PHT) is recognised as one of the top priority areas for the development of horticulture in India. Adoption of suitable PHT practices is important to reduce the huge post-harvest losses of horticultural commodities occurring in the country. The IIHR, Bengaluru, has developed several protocols and technologies in post-harvest handling and processing of different fruits, vegetable and flowers for their post–harvest loss reduction, extension of storage life and value-addition. Various protocols, technologies standardized and developed by the Institute includes selection of varieties of fruits, vegetables and flowers for fresh market and processing, pre-harvest treatments and post-harvest treatments to reduce post-harvest losses and extend shelf-life, extension of vase-life of cut flowers, development of diversified processed products like beverages, culinary pastes, dried and osmotic allydehydrated and de-hydro frozen fruits and vegetables, dehydration of flowers, improvement of wine quality, lactic acid fermentation and brine preservation, horticulture waste utilization. Several of these technologies have been transferred to farmers groups, entrepreneurs and industries for commercialization.